Return migration of foreign students - Govert Bijwaard; Qi Wang (Institute for the Study of Labor (IZA), 2013)
Using unique administrative micro panel data, this paper presents a comprehensive empirical analysis of the return of recent foreign students in The Netherlands. The life course experiences of these students in the host, both on the labour market and in marriage formation, impact their decision to leave. Using a timing-of-events model we estimate the impact of these processes on the return intensity. The model allows for correlated unobserved heterogeneity across the migration, the labour market and the marriage formation processes. The large size of the data permits us to stratify the analysis by five groups based on the country of birth. The empirical analyses reveal that employment induces students to stay and unemployment induces them to leave. Forming a family in The Netherlands makes the students more prone to stay. The size of the impact of these life course experiences on return differs by age at entry and gender.
Keywords: F22; J64; J12; C41; 330; student migration; timing of events method; labour dynamics; marriage